THU0293 PREDICTORS OF LONG-TERM THERAPY WITH GLUCOCORTICOID IN POLYMYALGIA RHEUMATICA. (2nd June 2020) - Aoki, A.; Kobayashi, H.
Abstract : Background: Polymyalgia rheumatica (PMR) is a common inflammatory condition of elderly persons. Clinical symptoms respond to low-dose glucocorticoids (GC), but treatment is often required for several years. 2015 EULAR/ACR recommendations 1) recommend considering early introduction of methotrexate (MTX) in addition to GC, particularly in patients at a high risk for relapse and/or prolonged therapy. However, risk factors for prolonged therapy are not clear yet. Objectives: We investigated predictive factors which corresponded to the long-term GC therapy. Methods: This was a retrospective study in a single general hospital in Japan. We reviewed the medical records of the Japanese patients with PMR between April 2011 and January 2020. Diagnosis of PMR was based on Bird's criteria or 2012 EULAR/ACR Classification Criteria 2) . All patients were treated with prednisolone (PSL), according to the BSR and BHPR guidelines 3), for more than 6 months. Patients treated with MTX and accompanied by the giant cell arteritis were excluded from this study. Relapse was defined as the reappearance of symptoms associated with elevated C-reactive protein (CRP) levels in patients receiving GC that required an increase in GC dose. Remission was defined as the absence of clinical symptoms and normal CRP with discontinuation of GC. We compared the clinical findings, laboratory data at baseline and clinical course between those who achieved remission within 2 years (early-remission group) and those who required GC therapy for more than 2 years (long-therapy group). Comparisons between groups were made using Student's t-test and chi-square test (IBM SSPE statistics version 26). This study was approved by the ethics committee of Tokyo Medical University (T2019-0079). Results: As of January 2020, 89 patients have been treated with PSL for more than 6 months. 50 patients have achieved a remission, 29 were undergoing treatment, and 10 have transferred to other hospitals or died (Table 1). The median time required for the patients to achieve remission was 16 months (Interquartile Range 12-21). After one-year GC therapy, remission was achieved in 14% (11/77), 66% (41/62) after 2-year, 84% (47/56) after 3-year, and 91.0% (49/54) after 4-years. Forty-one patients, who achieved remission within 2 years, were included in the early-remission group. Twenty-one were included in the long therapy group (Table 1). There were no differences in sex, age at onset, body mass index, clinical features, and serum albumin at diagnosis. Serum CRP of long-therapy group was significantly higher than those of the early-remission group (Table 2). Mean relapse times in the full follow-up times were 0.4 in the early-remission group and 3.1 in the long-therapy group. Multivariate logistic regression analysis showed that history of relapse till 6 months was significant predictors of the long-term GC therapy (odds ratio, 6.48; 95%CI 1.44-29.12). Conclusion: The remission rates of our study are lower than those of the previous reports. We have tapered GC gradually according to the BSR and BHPR guidelines 3) . However, some patients need the long-term therapy for more than 2 years. We might consider additional MTX therapy in patients who experience a relapse during the first six months. References: [1]Dejaco C, et al. 2015 recommendations for the management of polymyalgia rheumatica: a European League against Rheumatism/American College of Rheumatology collaborative initiative. Ann Rheum Dis 2015; 74:1799-1807. [2]Dasgupta B, et al: 2012 provisional classification criteria for polymyalgia rheumatica: a European League against Rheumatism/American College of Rheumatology collaborative initiative. Ann Rheum Dis 2012;71: 484-492. [3]Dasgupta, B, et al. BSR and BHPR guidelines for the management of polymyalgia rheumatica. Rheumatology 2010; 49:186-190. Disclosure of Interests: None declared